The American College: A Psychological and Social Interpretation of the Higher Learning.
DOI: 10.1037/11181-017
|View full text |Cite
|
Sign up to set email alerts
|

Fields of Study and the People in Them.

Abstract: College student curricular groups have been found to differ psychologically with respect to three main characteristics: intelligence, liberalism of attitudes, and psychological adjustment. 1 In each instance, the groups seem to be ordered in a systematic way. It is this systematic ordering that lends support to the hope that some basic understandings may come out of research in this area.Differences in mental abilities. The kind of difference among groups of students in various major fields that has been most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
(37 reference statements)
2
4
0
Order By: Relevance
“…The results pertaining to college major also fit a pattern observed previously, namely, that social science majors generally take a liberal stance, and people in applied fields are more conservative regarding many social attitudes (Bereiter & Freedman, 1962).…”
Section: Discussionsupporting
confidence: 85%
“…The results pertaining to college major also fit a pattern observed previously, namely, that social science majors generally take a liberal stance, and people in applied fields are more conservative regarding many social attitudes (Bereiter & Freedman, 1962).…”
Section: Discussionsupporting
confidence: 85%
“…The results confirm the predictions. First, social science students were more flexible than natural science students (significant type of major main effects) in agreement with numerous studies (e.g., Bereiter & Freedman, 1962;Goldschmid, 1967). More importantly, however, the primary hypothesis also was confirmed.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, longitudinal studies on the process of group socialization suggest that people internalize the attitudes and values, including negative intergroup attitudes and beliefs, of the group that they join (Guimond, 2000). For example, research indicates that students and faculty differ widely in their social and political views as a function of their academic discipline (see Bereiter & Freedman, 1962; Guimond, 1998; Guimond, Palmer, & Bégin, 1989; Ladd & Lipset, 1975; McClintock, Spaulding, & Turner, 1964; Sidanius, Pratto, Martin, & Stallworth, 1991). Accordingly, using a sample of 5,655 students from the University of Texas, Sidanius et al (1991) have shown that there are striking differences between career tracks on racism.…”
Section: Theoretical Predictionsmentioning
confidence: 99%